p90RSK pathway inhibition synergizes with cisplatin in TMEM16A overexpressing head and neck cancer - Abdulkader Yassin-Kassab; Suman Chatterjee; Nayel Khan; Nathaniel Wang; Vlad C. Sandulache; Eric H-B. Huang; Timothy F. Burns; Umamaheswar Duvvuri (BMC Cancer, 2024)
Abstract Head and neck squamous cell carcinoma (HNSCC) constitutes one of the most common types of human cancers and often metastasizes to lymph nodes. Platinum-based chemotherapeutic drugs are commonly used for treatment of a wide range of cancers, including HNSCC. Its mode of action relies on its ability to impede DNA repair mechanisms, inducing apoptosis in cancer cells. However, due to acquired resistance and toxic side-effects, researchers have been focusing on developing novel combinational therapeutic strategies to overcome cisplatin resistance. In the current study, we identified p90RSK, an ERK1/2 downstream target, as a key mediator and a targetable signaling node against cisplatin resistance. Our results strongly support the role of p90RSK in cisplatin resistance and identify the combination of p90RSK inhibitor, BI-D1870, with cisplatin as a novel therapeutic strategy to overcome cisplatin resistance. In addition, we have identified TMEM16A expression as a potential upstream regulator of p90RSK through the ERK pathway and a biomarker of response to p90RSK targeted therapy in the context of cisplatin resistance.